Relationship between programmed cell death and targeted therapy for thyroid cancer in patients with a poor prognosis: an update - Yuejia Zhao; Simeng Zhao; Zhe Fan; Yongfu Zhao; Guangzhi Wang (Discover Oncology)
Abstract In recent years, the incidence of thyroid cancer has steadily increased. However, the detailed mechanisms of pathogenesis are still unclear. Therefore, a comprehensive understanding of the underlying carcinogenesis mechanisms of thyroid cancer is required. Programmed cell death (PCD) is a cell death process mediated by specific molecular program, regulated by specific genes within the cell. Accumulating evidence suggests that PCD plays an indispensable role in thyroid cancer, maintaining intracellular stability by regulating genes and eliminating damaged or aged cells. In this review, we summarize six identified forms of PCD, analyze biomarkers for different PCD pathways in thyroid cancer, and briefly elucidate the roles of various PCD pathways in targeted therapies for thyroid cancers with a poor prognosis. We also provide an outlook on future treatments for drug-resistant thyroid cancer, poorly differentiated thyroid cancer, and iodine-refractory thyroid cancer, aiming to accurately identify targets and offer effective targeted therapeutic strategies.